Zwitterionic Polymer Coating Suppresses Microglial Encapsulation to Neural Implants In Vitro and In Vivo. Issue 6 (4th May 2020) - Yang, Qianru; Wu, Bingchen; Eles, James R.; Vazquez, Alberto L.; Kozai, Takashi D. Y.; Cui, X. Tracy
Abstract: For brain computer interfaces (BCI), the immune response to implanted electrodes is a major biological cause of device failure. Bioactive coatings such as neural adhesion molecule L1 have been shown to improve the biocompatibility, but are difficult to handle or produce in batches. Here, a synthetic zwitterionic polymer coating, poly(sulfobetaine methacrylate) (PSBMA) is developed for neural implants with the goal of reducing the inflammatory host response. In tests in vitro, the zwitterionic coating inhibits protein adsorption and the attachment of fibroblasts and microglia, and remains stable for at least 4 weeks. In vivo two‐photon microscopy on CX3CR1‐GFP mice shows that the zwitterionic coating significantly suppresses the microglial encapsulation of neural microelectrodes over a 6 h observation period. Furthermore, the lower microglial encapsulation on zwitterionic polymer‐coated microelectrodes is revealed to originate from a reduction in the size but not the number of microglial end feet. This work provides a facile method for coating neural implants with zwitterionic polymers and illustrates the initial interaction between microglia and coated surface at high temporal and spatial resolution. Abstract : Implanting neural electrode devices initiates inflammatory responses led by microglia, which compromise the recording or stimulation functions. A new strategy to coat zwitterionic polymer on silicon‐based neural electrode is developed and examined in vitro and in vivo, both showing a suppression of microglial response. In vivo two‐photon microscopy reveals smaller microglia end feet on zwitterionic‐coated electrodes than uncoated controls.